Amniocentesis and the risk of second trimester fetal loss in twin pregnancies: results from a prospective observational study. (October 2013) - Lenis-Cordoba, Natalia; Sánchez, María Ángeles; Bello-Muñoz, Juan Carlos; Sagalá-Martinez, Juan; Campos, Nazareth; Carreras-Moratonas, Elena; Cabero-Roura, Lluis
Abstract Aim: To compare the rate of pregnancy loss between twin pregnancies undergoing a genetic amniocentesis (AC) and a control group with similar characteristics. Methods: Prospective observational study on a population of twin pregnancies referred to our prenatal diagnosis unit for screening from 1990 to 2010. Those women referred for an AC were compared with those without indication for the procedure. Primary outcomes were pregnancy loss within the 4 weeks after procedure and pregnancy loss before 24 weeks. Secondary outcome included neonatal morbidity, gestational age at delivery and birth weight. Results: Maternal characteristics were similar for both groups, except for maternal age. There was neither difference in the pregnancy loss rate within 4 weeks (2.7 versus 2.6%) nor in the loss rate before 24 weeks of gestation (1.2 versus 1.1%). Gestational age at birth was 36 weeks for both groups. Chorionicity and gestational age at procedure played no role in modifying the risk. Conclusion: Based on our results, there is no difference in the pregnancy loss rate in twin gestations, regardless of chorionicity or gestational age at procedure, either within 4 weeks after the procedure or before 24 weeks, in patients who undergo AC when compared with patients who do not.